USING THE METHOD OF ANALOGIES IN THE PROCESS OF LEARNING NATURAL SCIENCES - Stepanyuk, Alla; Sarabuna, Irina (SWorld-Ger Conference proceedings, 2023)
The problem of using the method of analogy in the process of studying natural sciences in institutions of general secondary education is updated. On the basis of the study of practice, it was concluded that it is still an underdeveloped direction in didac